Purification and Properties of Glycogen Isolated from a Blue-Green Alga, Nostoc muscorum - Chao, Lee (1971)
Alpha granules were isolated from a blue-green alga, Nostoc muscorum, in large quantities and high purity by sucrose density gradient centrifugation. Sodium deoxycholate was used to eliminate membrane contamination. Isolated α granules from this species have average dimension of 31 nm in width and 65 nm in length. Each α granule consists of two equal parts. Attempts to dissociate the intact granule under mild conditions into relatively large subunits did not succeed. Analytical centrifugation of the α granules yields a sedimentation coefficient of 265S (S(20, w)). Chemical analysis reveals that α granules contain highly branched polyglucosyl units with short external chain lengths.